Combination of Ispring Suite and Chamilo in Creating Online Math Assessments - Chairuddin, Chairuddin; Nasrum, Akbar (IJBLE Scientific Publications Community Inc., 2023)
Technology in learning is developing very rapidly regarding material delivery and assessment or evaluation. An educator needs to possess the ability to compose good assessments to measure the success of students' understanding of the material. With the development of technology, educators should be able to transform conventional assessments into digital assessments to support the digitalization process in education. The main objective of this research is to create an assessment tool for mathematics courses using the Ispring Quiz Maker and then integrate it into Chamilo. The combination of quiz maker software and LMS will add insight to readers, especially teachers and lecturers, in making online mathematics assessments. A modified development method from ADDIE, 4D, and Plomp was used to achieve this goal. The several stages passed resulted in an assessment prototype for the Differential Calculus course. The resulting assessment instrument has gone through the item and material validation processes to obtain a good instrument that is suitable for use. This instrument can later be used for the Final Semester and Midterm examinations for Differential Calculus courses.